Patient Needs and Environments for Cancer Infusion Treatment. Issue 2 (28th January 2017) - Wang, Zhe; Pukszta, Michael
ABSTRACT: More than 50% of cancer patients receive chemotherapy by infusion, which is typically delivered in ambulatory healthcare settings. Influences of the built environment on inpatient care are well documented, but environmental research focusing on ambulatory healthcare is lacking. This empirical research focuses on cancer infusion environments and reveals important patient needs linking the built environment to infusion care. A survey of 166 patients and observations of 252 patients were conducted in an academic cancer center to explore patient preferences on private, semiopen, or open environments for infusion treatment and the reasons for their preferences. The observations investigated patient interactions with the environments during infusion treatment. Findings from qualitative and quantitative data analyses showed that private, semiopen, or open spaces were generally equally popular among patient participants. Needs for high‐level privacy, quiet places to nap or sleep, social interaction, patient–nurse access, sunshine, and views to the outside were identified as major reasons for patient preferences. Items important to patients during treatment included patient chair tablets, guest chairs, personal televisions, nap blankets, food or beverages, window views, and sunshine. Participants with access to positive window views reported significantly lower levels of stress and greater hope for successful treatment than their counterparts ( p < .05). Findings suggest that important environmental features of ambulatory healthcare settings are both similar to and different from that of inpatient environments in the way they significantly impact the quality and experience of care.